DECISION SUPPORT SYSTEM TO CHOOSE SMARTPHONE USING TOPSIS METHOD - Agung Hamdika Surya; Ilka Zufria; Yusuf Ramadhan Nasution (Sean Institute, 2021)
Technology has developed very rapidly nowadays, especially on smartphones. Nowadays smartphone is an item that is in great demand by everyone. smartphone is a mobile phone that has a function like a computer and also called mini computer. There are people who find it difficult to choose a smartphone with various advanced features available. Therefore, a decision support system was made using the TOPSIS method to select the smartphone that suits your needs. TOPSIS (Technique for order prefrence by similarity to ideal solution) is one of the multi-criteria decision making methods to find preference values ​​based on criteria and alternatives. A total of 7 criteria chosen by the author that are: price, brand, ram, battery, front camera, rear camera and display. Therefore, the alternatives used are Samsung A20, Xiaomi Mi A1, Realme C2, Asus Zenfone Max M2 and Oppo F5 Youth. The data is then calculated using the TOPSIS method based on the stages. So that we can get the preferences value and the rank of the smartphone we wanted which is then implemented into a web-based application. Keywords : Smartphone, TOPSIS, DSS